Effects of tocilizumab and dexamethasone on the downregulation of proinflammatory cytokines and upregulation of antioxidants in the lungs in oleic acid-induced ARDS - Terzi, Funda; Demirci, Beste; Çınar, İrfan; Alhilal, Mohammad; Erol, Huseyin Serkan (Springer Science and Business Media LLC, 2022)
Abstract Background Acute respiratory distress syndrome (ARDS) is a life-threatening disease caused by the induction of inflammatory cytokines and chemokines in the lungs. There is a dearth of drug applications that can be used to prevent cytokine storms in ARDS treatment. This study was designed to investigate the effects of tocilizumab and dexamethasone on oxidative stress, antioxidant parameters, and cytokine storms in acute lung injury caused by oleic acid in rats. Methods Adult male rats were divided into five groups: the CN (healthy rats, n = 6), OA (oleic acid administration, n = 6), OA + TCZ-2 (oleic acid and tocilizumab at 2 mg/kg, n = 6), OA + TCZ-4 (oleic acid and tocilizumab at 4 mg/kg, n = 6), and OA + DEX-10 (oleic acid and dexamethasone at 10 mg/kg, n = 6) groups. All animals were euthanized after treatment for histopathological, immunohistochemical, biochemical, PCR, and SEM analyses. Results Expressions of TNF-α, IL-1β, IL-6, and IL-8 cytokines in rats with acute lung injury induced by oleic acid were downregulated in the TCZ and DEX groups compared to the OA group (P < 0.05). The MDA level in lung tissues was statistically lower in the OA + TCZ-4 group compared to the OA group. It was further determined that SOD, GSH, and CAT levels were decreased in the OA group and increased in the TCZ and DEX groups (P < 0.05). Histopathological findings such as thickening of the alveoli, hyperemia, and peribronchial cell infiltration were found to be similar when lung tissues of the TCZ and DEX groups were compared to the control group. With SEM imaging of the lung tissues, it was found that the alveolar lining layer had become indistinct in the OA, OA + TCZ-2, and OA + TCZ-4 groups. Conclusions In this model of acute lung injury caused by oleic acid, tocilizumab and dexamethasone were effective in preventing cytokine storms by downregulating the expression of proinflammatory cytokines including TNF-α, IL-1β, IL-6, and IL-8. Against the downregulation of antioxidant parameters such as SOD and GSH in the lung tissues caused by oleic acid, tocilizumab and dexamethasone upregulated them and showed protective effects against cell damage.
Keywords: Male; Acute Lung Injury; Down-Regulation; Antibodies, Monoclonal, Humanized; Antioxidants; Dexamethasone; Diseases of the respiratory system; Animals; Lung; Respiratory Distress Syndrome; RC705-779; Interleukin-6; Superoxide Dismutase; Tumor Necrosis Factor-alpha; Research; Interleukin-8; ARDS, Tocilizumab, Dexamethasone, Oleic acid, Rat; Tocilizumab; Oleic acid; Rats; Up-Regulation; Rat; Cytokines; ARDS; Cytokine Release Syndrome; Oleic Acid; 3. Good health